Validation of the French version of the P-QoL questionnaire. (September 2015) - Veit-Rubin, Nikolaus; Digesu, Alex; Swift, Steven; Khullar, Vik; Kaelin Gambirasio, Isabelle; Dällenbach, Patrick; Boulvain, Michel
Abstract: Objective: The aim of this study was to validate a French version of the prolapse-quality-of-life-questionnaire (P-QoL). Study design: The P-QoL was translated into French and administered to patients recruited in a tertiary referral teaching Hospital. The women concomitantly had a vaginal exam in supine position in order to determine prolapse stage using Pelvic Organ prolapse quantification system (POP-Q). The reliability was assessed by calculating Cronbach's alpha and by performing a test–retest analysis. The validity was evaluated by comparing scores for symptoms and quality of life between symptomatic and asymptomatic women as well as by comparing symptom scores with prolapse stages. Results: 25 symptomatic and 22 asymptomatic patients were included. Cronbach's alphas and the test–retest analysis showed acceptable internal consistency within the domains. The total scores for seven P-QoL domain were significantly different between symptomatic and asymptomatic women ( p < 0.005). The scores of P-QoL were well correlated with the vaginal examination findings among the symptomatic group ( p < 0.05 in seven domains). Conclusion: The French version of P-QoL is a reliable, valid, and easily comprehensible instrument to assess quality of life and symptoms in women with pelvic organ prolapse.